SOIL FERTILITY MANAGEMENT OF ESTABLISHED BER (ZIZIPHUS MAURITIANA) PLANTATION UNDER LAC CULTIVATION - S. GHOSAL (The Bioscan, 2013)
Lac cultivation is a profitable option of agriculture for the farmers of Jharkhand, Chhattisgarh, Odisha, Madhya Pradesh, West Bengal etc. An experiment comprising different levels of liming (liming and no liming), nitrogen (0, 100, 200 and 400g/tree), phosphorus (0 and 150g/tree) and potassium (0 and 150g/tree) to make 32 treatment combinations replicated thrice was launched in the research farm of Indian Institute of Natural Resins and Gums, Ranchi (23º23’N longitude, 85º23’ E latitude and 650m above MSL) during 2007-10 to generate information on level of soil fertility required to sustain growth of the tree under kusmi lac cultivation in the winter season. Findings of the experiment indicated that under control condition, the average bio-mass production per tree started reducing @ 0.81kg/ year and with application of 400g nitrogen, 150g each of phosphorus and potassium along with liming could increase bio-mass production per tree @ 4.36kg/ year under lac cultivation. Chlorophyll Content Index (CCI) was significantly affected by liming. At 45 days after fertilizer application, lime applied trees registered 10 percent increase in chlorophyll content index. Similarly, potassium application could lower shoot dry matter by 1.76 percent, i.e. shoot succulency increased. Experimental data revealed that nitrogen application upto 200 g/ tree did not influence termite infestation significantly. However, rates beyond it increased infestation significantly. Due to liming, soil available potassium level, organic carbon, electrical conductivity and pH increased by 12, 7, 12 percent and 0.11 units, respectively. Therefore, increases in growth attributes have been observed under liming.